The new authoritarianism : Trump, populism, and the tyranny of experts - Babones, Salvatore J. (Cambridge, UK ; Polity, 2018)
"In this provocative and highly original book, Salvatore Babones argues that democracy has been undermined by a quiet but devastating power grab conducted by a class of liberal experts. Populism thus represents an imperfect but reinvigorating political flood that has the potential to rejuvenate democracy across the west"--
Includes bibliographical references and index.
Keywords: Liberalism; Populism; Democracy; SOCIAL SCIENCE / Sociology / General